Keabsahan Akta Hibah Yang Digunakan Wajib Pajak Untuk Penghindaran Pajak - Maharani, Mentari Rizkika; Wijaya, Vira; Sinawan, Carolina Isabela; Salsabila, Aurynanda; Alvina, Zenza Ayu (JURNAL USM LAW REVIEW, 2025)
The aim of this research is to analyze the validity of gift deeds made by taxpayers with the aim of avoiding tax, by reviewing the role of Notaries in ensuring the legality of gift deeds as well as the relevance of tax provisions related to gifts of property which are part of the Notary's duties and responsibilities. The background of this research is based on several cases that occurred, namely related to the transfer of assets through gifts which are often used to avoid tax obligations. One of the prominent cases is the manipulation of gifts by a taxpayer with the initials TY, a Supreme Court judge, who during the investigation found that the addition of assets was not reasonable and many were made through gifts. The urgency of this writing lies in the importance of ensuring that the gift deed made by the Notary does not violate the law, considering that the Notary is a public official who is responsible for compiling and making authentic deeds. The research method used is normative juridical, with an analytical approach to applicable legal regulations. The research results show that gifts from equal family members who are not related to business are not subject to tax, considering that the practice of giving is often used for tax avoidance, the Notary needs to understand the tax rules related to gifts and sanctions for violations so that the gift deed prepared can be legally accounted for. The novelty of this research is that it identifies notary’s role and analyzes loopholes in regulations that allow taxpayers to take advantage of gift deeds to avoid tax obligations considering that familial grant transactions are often difficult to verify, thereby allowing for misuse by taxpayers.Tujuan penelitian ini adalah untuk menganalisis keabsahan akta hibah yang dibuat oleh wajib pajak dengan tujuan menghindari pajak, dengan meninjau peran Notaris dalam memastikan legalitas akta hibah serta relevansi ketentuan perpajakan terkait hibah harta yang menjadi bagian dari tugas dan tanggung jawab Notaris.  Latar belakang penelitian ini didasarkan pada beberapa kasus yang terjadi yaitu terkait pengalihan harta melalui hibah yang kerap digunakan untuk menghindari kewajiban pajak. Salah satu kasus yang menonjol adalah manipulasi hibah oleh wajib pajak berinisial TY seorang hakim agung yang dalam pemeriksaan ditemukan penambahan harta yang tidak wajar dan banyak dilakukan melalui hibah. Urgensi penulisan ini terletak pada pentingnya memastikan akta hibah yang dibuat oleh Notaris tidak melanggar hukum, mengingat Notaris adalah pejabat umum yang bertanggung jawab untuk menyusun dan membuat akta autentik. Metode penelitian yang digunakan adalah yuridis normatif, dengan pendekatan analisis peraturan hukum yang berlaku. Hasil penelitian menunjukkan bahwa hibah dari anggota keluarga yang setara dan tidak terkait bisnis bukan merupakan subjek pajak, mengingat praktik hibah sering kali dimanfaatkan untuk penghindaran pajak maka Notaris perlu memahami aturan perpajakan terkait hibah dan sanksi atas pelanggaran agar akta hibah yang disusun dapat dipertanggungjawabkan secara hukum. Kebaruan dalam penelitian ini adalah mengidentifikasi peran Notaris dan menganalisis celah-celah dalam regulasi yang memungkinkan wajib pajak memanfaatkan akta hibah untuk menghindari kewajiban perpajakan mengingat transaksi hibah yang bersifat familial sering kali sulit diverifikasi sehingga memungkinkan penyalahgunaan oleh wajib pajak.
Keywords: Keyword; Grant Deed; Tax; Notary